Determinants of Health Workers Compliance in Implementing EMR in Regional Hospitals in Bali - Luh Gde Nita Sri Wahyuningsih; Ni Luh Putu Dina Susanti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Electronic Medical Records (EMRs) refer to the digitization of medical documentation and associated processes, aimed at enhancing data completeness and accuracy. This study examined the compliance of health workers with EMR system implementation. The research was conducted at Klungkung Regency Hospital in Bali, involving 520 participants, including general practitioners, specialists, nurses, midwives, medical record officers, health analysts, pharmacists, nutritionists, and radiographers. Data were collected using a structured questionnaire distributed via Google Forms, employing a total sampling technique. The findings revealed that several factors, namely competence in information technology, system knowledge, perceived benefits and ease of use, as well as organizational support and training, were significantly associated with EMR implementation. Among these, system knowledge exerted the strongest influence, with an Adjusted Odds Ratio (AOR) of 3.549. This suggests that respondents with a high level of system knowledge were over three times more likely to implement EMRs effectively compared to those with limited understanding. Knowledge plays a pivotal role in preparing health workers for technological adaptation. Those with sufficient knowledge are better equipped to navigate system features and apply them in accordance with established standard operating procedures. Health workers who possess a strong understanding of EMRs tend to be more receptive to adopting the system, underscoring the importance of comprehensive training and education. Enhancing knowledge through targeted training, socialization, and continuous professional development is essential to ensure the successful implementation and optimal utilization of EMRs in healthcare settings Keywords: Electronic Medical Record, Health Worker Compliance